O jornal em sala de aula: intervenção com o gênero charge - Rodrigues, Reno (2016)
The genres of the journalistic sphere have a great social relevance and its circulation occurs quite broadly, even within other discursive domains, as it happens in school. The Portuguese National Curriculum Parameters themselves recommend a work with argumentative genres of this sphere of circulation, for whom their discursive domain is of fundamental importance for the effective insertion in social circles. Thus, our research developed a pedagogical intervention in a class of Elementary School II from the cartoons that are published daily in the newspaper Tribuna do Norte. For this, we used the didactic sequence model proposed by Schneuwly and Dolz (2013). The choice of the present gender as object of study came from the students participating in this research, after the application of a questionnaire. In our view, the genre charge serves the purposes of this research, since it is a multimodal statement, whose hybrid and attractive language commonly instigates the reader's imagination and also because it is a genre of argumentative character, the reading of which may enlarge Ability of the student. Thus, the aim of the work was to propose reading strategies that allow students to effectively understand the genre textual charge. The corpus of this research concerns a reasonable universe of cartoons by the cartoonist Rodrigo Brum Machado, which were worked in the reading and comprehension workshops as well as anchoring to associate the theoretical reference adopted in this research. We analyzed the multimodal aspects, global aspects, such as the universe of reference, semantic unity (thematic), communicative purpose, informative relevance and its relations with other texts. Our work is part of the study area of Applied Linguistics and the methodological approach adopted is based on a qualitative-interpretative research, focusing on action research, in which we apply to the students a Teaching Sequence (SD). We adopted as reference the studies of Antunes (2013), Bakhtin (2015), Cavalcante (2014), Koch (2014), Marcuschi (2012), Dionísio (2012), Vieira (2007), Romualdo , Bortoni-Ricardo (2013) and Thiollent (2013). One of our research questions brought us reflection on the difficulty of reading our students in front of the multimodality genres. The work with the genre charge gave the participants some benefits, although still incipient, in what concerns the development of their capacities of critical reading in relation to the text constituted by more than one mode of representation.